METHOD OF PROJECT SASA NEW METHOD OF INDEPENDENT WORKSTUDENTS - Пиптюк, О. В.; Телемуха, С. Б.; Пиптюк, В. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
A research aim is development of creative skills in research work of students, studies of their information retrieval and work with literature and patient, integration of knowledge in medicine and development of the clinical thinking. Practice of naturally-scientific preparation of medical workers testifies in higher educational establishments, that the use of traditional didactics facilities and methods does not provide intensive development of cognitive activity, individual capabilities and professional knowledge of students. . Overcoming of these contradictions is possible on condition of the use of new approaches to forming of knowledge of students. Practically in each of on-line tutorials the envisaged hours for independent work of students. Control of quality of independent work of students a teacher is practically impossible. The decision of problem is possible through the use of interactive methods of studies, one of that there is a method of projects. A project method of studies is totality of such methods of studies, at that students by means of collective or individual activity from a selection, distribution and systematization of material from a certain theme, fold a project. Conclusions: introduction of method of projects in an educational process in the conditions of the credit-module system sent to the system forming of knowledge of students of physicians, that will be able to decide a task in the different spheres of practical professional activity.